Empirical Evaluation of Short-Range WiFi Vessel-to-Shore Overwater Communications - d'Orey, Pedro (2022)
Unmanned vehicles used in ocean science, defense operations and commercial activities collect large amounts of data that is further processed onshore. For real-time information exchange, the wireless link between the unmanned vehicle and onshore devices must be reliable. In this work, we empirically evaluate a WiFi link between an autonomous underwater vehicle on the surface and an onshore device under real-world conditions. This work allowed i) collecting a large-scale realistic dataset and ii) identifying major factors impairing communication in such scenarios. The TX-RX antenna alignment, the operation mode (manual vs automatic) and varying reflecting surface induced by AUV mobility lead to sudden changes (e.g. nulls) in the received signal strength that can be larger than 20 dB. This study provides useful insights to the design of robust vessel-to-shore short-range communications.